1976
DOI: 10.1021/jo00870a007
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of benzothiazole and substituted benzothiazoles with dimethyl acetylenedicarboxylate. A novel heterocyclic ring transformation

Abstract: Reaction of benzothiazole with dimethyl acetylenedicarboxylate in aqueous methanol gives irons-dimethyl 4formyl-2,3-dihydro-l,4-benzothiazine-2,3-dicarboxylate in high yield, and a mechanism is proposed for this novel transformation. The scope and limitations of the process have been defined by examination of the reactions of a wide range of substituted benzothiazoles with dimethyl acetylenedicarboxylate in aqueous methanol; the results are fully consistent with the postulated mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0
2

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
0
6
0
2
Order By: Relevance
“…In fact, for now, four approaches to BTAs III are known [21][22][23][24][25] (Scheme 2). They include the reaction of dimethyl acetylenedicarboxylate (DMAD) with o-aminothiophenol (1a) on the catalyst SiO 2 @H 3 PW 12 O 40 [21], the reaction of tetracarbonyl compounds with o-aminothiophenol (1a) [22,23], the Scheme 1: Reported structure A of assayed compound [9] and its correct structure B.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, for now, four approaches to BTAs III are known [21][22][23][24][25] (Scheme 2). They include the reaction of dimethyl acetylenedicarboxylate (DMAD) with o-aminothiophenol (1a) on the catalyst SiO 2 @H 3 PW 12 O 40 [21], the reaction of tetracarbonyl compounds with o-aminothiophenol (1a) [22,23], the Scheme 1: Reported structure A of assayed compound [9] and its correct structure B.…”
Section: Introductionmentioning
confidence: 99%
“…reaction of copper(II) chelate of ethyl pentafluorobenzoylpyruvate with o-aminothiophenol (1a, one example) [24] and the reaction of DMAD with 6-nitro-1,3-benzothiazole (one example) [25]. Our recent research [26] revealed that the approach based on the reaction of tetracarbonyl compounds with o-aminothiophenol (1a) [22,23] is a mistaken one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Despite their importance from pharmacological, industrial, and synthetic point of view, comparatively few methods for their preparation were reported. Some of the methods reported in the literature for the synthesis of oxazine derivatives are McKillop cycloaddition, 11 N-and O-alkylation with dibromo compounds, 12 lithiation method, 13 use of chiral epoxides under phase transfer catalysts. 14 However, very few methods are available for the synthesis of 1,4-benzoxazinone or 1,4-pyridooxazinone derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…τολουόλιο,139 . Η μονοξίμη(121) δεν αντέδρασε κατά τη θέρμανση της σε τολουόλιο, ενώ κατά την επίδραση του ημισταθερού υλιδίου (47) έδωσε το αντίστοιχο οζαζολικό παράγωγο (122) 139 . R 122 Κατά την αντίδραση της (111) με το υλϊδιο Ph 3 P=CHCOCH 3 (68) ελήφθη μίγμα πολλών προϊόντων σε μικρές αποδόσεις και μη διαχωριζομένων 136 .…”
unclassified